Risk factors and reinsurers’ performance: Analyzing the effects of underwriting, operational, retention, and investment risks on reinsurers in Nigeria - Usman, Aishat Oladunni; Obalola, Musa Adebayo (Jurnal Ekonomi KIAT, 2025)
Purpose: This research investigated the impact of underwriting, operational, retention and investment risks on profit after tax and return on assets of reinsurers. Design/methodology/approach: The study used an ex-post facto research design using quarterly time series data of the selected reinsurance company for a 13-year period from 2013 to 2024. Eviews 9 was used to perform descriptive analysis, correlation analysis, unit root test and regression analysis to test the effects of the underwriting, operational, retention and investment risks on the profit after tax and return on assets of reinsurers. Findings: The results revealed that underwriting, operational and retention risks have negative and insignificant effects on return on assets. The effects of the trio on profit after tax is negative but significant. Investment risk has positive and significant effect on both return on assets and profit after tax of reinsurers. This shows that high underwriting, operational, retention risks reduce the profitability of reinsurer while high investment risk increases reinsurers’ profitability there by cushioning the effect of the other risks on profitability. Limitations and Research implications: As the paper relied heavily on secondary data, primary empirical validation is limited. Future research should include field studies or surveys to validate the conceptual framework and explore sector-specific challenges in greater detail. Practical Implications: Understanding the collective and individual impact of underwriting, operational, Investment and retention risks allows reinsurers to better manage and mitigate their exposure. Originality/value: This study fills the literature gap on studies on risk and reinsurer’s performance as most of the existing studies focused on risk and insurers’ performance leading to paucity of research on risk and reinsurers’ performance.